Prevalence and Associated Factors of Canine Visceral Leishmaniasis in an Endemic Area of Mato Grosso, Brazil - Fujimori, Mahyumi; Almeida, Arleana do Bom Parto Ferreira de; Dias, Álvaro Felipe Lima Ruy; Rodrigues, Juliana Yuki; Nakazato, Luciano; Madeira, Maria de Fátima; Sousa, Valéria Régia Franco (Acta Scientiae Veterinariae, 2016)
Background: Canine visceral leishmaniasis is a chronic and severe disease of great interest to global public health. In Brazil, the main species causing visceral leishmaniasis is Leishmania chagasi [syn. Leishmania infantum], which is transmitted by sandflies of the species Lutzomyia longipalpis and Lu. cruzi. This study aimed to determine the risk factors and prevalence of visceral leishmaniasis in dogs residing in endemic areas of the municipality of Várzea Grande, Mato Grosso. Material, Methods & Results: The study was conducted in the Várzea Grande neighbourhoods Jardim Eldorado, Parque Sabiá and São Mateus, which are located in the Brazilian Cerrado region and are endemic for visceral leishmaniasis. The Várzea Grande is a mostly commercial and industrial municipality and relies on subsistence farming. To describe the general characteristics of the dog population and housing environment, an interview was carried out with the dog owners in each household. This interview addressed local demographics and the identification of dogs to establish epidemiological aspects of canine illness and risk factors for infection. The dogs were examined and physically restrained for blood collection by jugular venipuncture. For serological testing, a commercial enzyme-linked immunosorbent assay (ELISA) was used. A Chi-square test or Fisher’s exact test was used to identify associations between independent variables and the seroprevalence of dogs with anti-Leishmania antibodies. It were collected blood from 521 animals, including 160 belonging to Jardim Eldorado, 129 to Parque Sabiá and 232 to São Mateus. Of these animals, 120 were reactive by ELISA, with a prevalence of 23.0%. There was no statistically significant difference (P > 0.05) according to gender, age, racial definition, origin, time with family, presence of ectoparasites, or the presence of people with skin wounds at home or on other pets. The major risk factor for canine infection was fur length; dogs with short fur were 2.2 times more likely to be infected than dogs with long fur. Discussion: The prevalence of canine leishmaniasis in endemic areas was found to be similar to studies in Cuiaba, a city in Várzea Grande, which also included neighbourhoods endemic for visceral leishmaniasis as study areas. Other studies have shown prevalence rates that differ from those found in this study. This difference may either be because the neighbourhoods in this study had already experienced outbreaks of the disease or because serum samples were cross-reactive with other trypanosomatids. While infection was more readily detected in dogs with clinical signs, asymptomatic dogs with anti-Leishmania antibodies were found in greater numbers, which is consistent with the literature. Hair length was the only factor associated with canine leishmaniasis in this study; short-haired animals were most at risk of contracting the disease because they had more skin exposure to sandflies during blood feeding. In conclusion, endemic districts of Várzea Grande had high prevalence rates of canine visceral leishmaniasis, and a short length coat was associated with infection.